For Sale - Welsh, Savannah (Auckland University of Technology, 2019)
My thesis is focused on child sex trafficking, including online child sex trafficking. The research is mostly based on American statistics, setting, and real life events/victims, with the inclusion of other cultures and the different areas of human trafficking, such as slave labour and forced child labour. I have gathered research from online sources, documentaries, films, and other literature.
Keywords: Trafficking; Human rights; Crime; Sex trafficking